Wacana Moderasi Beragama Berdasarkan Dalil Naqli dan Akli - Mutiara Hardewita (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
Religion is a form of belief in God and interaction with God. It is not uncommon to find that many conflicts occur in the coexistence of differences due to religious beliefs and their respective religious practices. The Qur'an as a naqli argument contains rules of life in it, as well as regarding the command to behave which is the term religious moderation and gives rise to the discourse of religious moderation based on the rational argument. This research is a type of qualitative research by obtaining data through literature studies with descriptive analysis methods. This writing is used to find out what the discourses of religious moderation are in the naqli argument and based on the rational argument. The purpose of this study is to analyze the discourse of religious moderation in the naqli argument and the rational argument. The results state that religious moderation appears and is explained in the Qur'an from the phenomenon of nationality, religious moderation as a middle ground, as tolerance, and is a concept of balance and justice, and based on the rational argument, where religious moderation is explained from the existence of extremism and fanaticism. Not only from the naqli propositions which are the source of written law, religious moderation can also be explained simultaneously with the akli propositions which can be accepted by reason.